Response of laminated glass elements subject to dynamic loadings using a monolithic model and a stress effective Young's modulus. (May 2022) - Aenlle López, Manuel; Fernández, Pelayo; Álvarez-Vázquez, Adrián; García-Fernández, Natalia; Muñiz-Calvente, Miguel
Due to the brittle nature of the glass, to study the response of glass elements subjected to dynamics loadings is of great interest, mainly when human injury resulting from glass breakage may occur. Laminated glass consists of two or more layers of monolithic glass and one or more viscoelastic interlayers. In this paper, a technique to predict the dynamic response (deflections and stresses) of laminated glass elements using a linear elastic monolithic model is proposed and validated. In a first step, the modal parameters and the dynamic response of a monolithic model are calculated using the modal superposition technique. Then, the modal parameters and the modal coordinates of the laminated glass element are estimated using the equations derived in this paper. Finally, the stresses in time and frequency domain are estimated using an effective stress Young's modulus.